Современные проблемы горно-металлургического комплекса Украины - Большаков, В.И.; Тубольцев, Л.Г.; Плискановский, С.Т. (Металл и литье Украины, 2013)
Дана оценка перспектив развития горно-металлургического комплекса Украины с учетом его современного состояния и параметров, характеризующих состояние мировой металлургии. На основе анализа тенденций развития металлургии определены направления и задачи научных исследований, сформулированы предложения по развитию отечественной металлургии. Дано оцінку перспектив розвитку гірничо-металургійного комплексу України з урахуванням його сучасного стану та параметрів, що характеризують стан світової металургії. На основі аналізу тенденцій розвитку металургії визначено напрями та задачі наукових досліджень, сформульовано пропозиції щодо розвитку вітчизняної металургії. The aim of this study is to assess the prospects of the development of mining and metallurgical complex of Ukraine taking into account its current state and parameters characterizing the state of the global steel industry(metallurgy). Based on analysis of industry trends development are identified directions and aims of scientific researches, also are generated proposals for the development of domestic metallurgy.